O romance de mistério e o mistério do romance - Pessoa, Rosane Rocha (1989)
This study aims to decipher the formal and thematic "mysteries" of five Brazilian narratives which deal with crime. Be ggining with the structure of trivial narratives ~ characteristic of the classical police stories ~, it is verified how the crimina l intrigue is presented in the five narratives. nesides deviating from the scheme, they question the involving criminal reality. It is, in my view, the "humanization" of a trivial theme because they elaborate on contradiction as its fundamental structure . This dialetic elaboration answers for the amplification of the criminal matter, permitting the approach of philosophycal, social, economic, mystic and moral themes. Under this scope, the five place themselves in opposition narra tives to the rheification and alienation imposed by the cultural industry.